Kontribusi Pola Asuh Terhadap Perilaku Prososial Siswa Kelas VIII SMP Negeri 57 Jakarta - Priska Dini Alfita; Budiaman Budiaman; Sujarwo Sujarwo (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Prosocial Prosocial behavior needs to be owned by adolescents as a foundation for the development of their social skills. Parental parenting style is one of the factors that influences prosocial behavior itself. The aim of this research is to find out how parental parenting influences the prosocial behavior of class VIII students at SMPN 57 Jakarta. This research uses a correlational approach with a non-experimental quantitative approach. The sample consisted of 140 respondents, selected through a simple random sampling. The questionnaire distribution method was used to obtain data. The research results showed that parenting style had a significant influence of 14.4% on the prosocial behavior of class VIII students at SMPN 57 Jakarta, with a calculated t value (4.814) > t table (1.656) and a significance value (0.000) < 0.05.